Effect of LED Light Color on Color Brightness, Growth, and Survival of Comet Fish (Carassius auratus) - Nisa, Baiq Haerun; Cokrowati, Nunik; Scabra, Andre Rachmat (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Comet fish (Carassius auratus) is a type of freshwater ornamental fish with a high selling value due to its unique body shape and bright colour. The purpose of this study was to evaluate the effect of different LED (Light Emitting Diode) light colours on colour brightness, growth, and survival of comet fish. This study applies an experimental approach with an experimental design in the form of a completely randomized design (CRD) and consists of 5 light treatments and 3 replications, namely A (room light), B (white LED), C (blue LED), D (green LED), and E (red LED). The results showed that LED light treatment had a significant effect on the colour quality and feed efficiency, but did not significantly affect the growth and survival of comet fish. The best colour quality was found in treatment E (red LED) with an increase in the TCF (Toca Color Finder) score of 6.22 and colour performance on the back by 80.80%, pectoral fin colour by 64.91%, and tail fin by 71 .18%. The best feed efficiency was obtained in treatment C (blue LED) with a feed efficiency value of 57.48%. The behavioural responses of comet fish did not make any difference between each LED treatment. The water quality of the comet fish rearing media has a temperature value ranging from 25.70 – 29.20 C. The pH value ranges from 7.29 to 8.50. Meanwhile, dissolved oxygen ranges from 8.00 – 12.20 mg/L.